1989
DOI: 10.1200/jco.1989.7.10.1573
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemia in patients treated with recombinant interleukin-2: appearance of remnant-like lipoproteins.

Abstract: Reversible acute hypocholesterolemia was observed during treatment of metastatic cancer with high-dose intravenous recombinant interleukin-2 (IL-2). Further analysis revealed virtual disappearance of high-density lipoproteins (HDLs) and marked reduction in the concentration of low-density lipoproteins (LDL); the remaining LDL and intermediate-density lipoproteins (IDL) were enriched in triglyceride relative to cholesterol and had broad-beta electrophoretic mobility, properties reminiscent of remnant lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Therefore, this study confirms also with low-dose IL-2 subcutaneous therapy the results previously described by other authors (Wilson et al, 1989) with very high doses of IL-2 given intravenously. The IL-2 cholesterol-lowering activity seems to be more rapid and pronounced than that of 3-hydroxyl-3-methylglutarilcoenzyme A (HMG-CoA) reductase inhibitors (Tobert, 1987), and comparable to that observed with GM-CSF (Nimer et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, this study confirms also with low-dose IL-2 subcutaneous therapy the results previously described by other authors (Wilson et al, 1989) with very high doses of IL-2 given intravenously. The IL-2 cholesterol-lowering activity seems to be more rapid and pronounced than that of 3-hydroxyl-3-methylglutarilcoenzyme A (HMG-CoA) reductase inhibitors (Tobert, 1987), and comparable to that observed with GM-CSF (Nimer et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…However, the IL-2-induced hepatic function damage, as documented by the increase in transaminases and in gamma-GT, could also play a role in determining a reduced cholesterol synthesis, whereas .11^%-other factors, including leukocyte proliferation (Rosenberg et al, 1987) and cortisol rise (Denicoff et al, 1989) induced by IL-2, would not be enough to explain the rapid and very pronounced fall in cholesterol levels, which occurs within few days from the start of IL-2 therapy, and precedes leukocyte proliferation. The progressive decline with time in IL-2 cholesterollowering activity, observed in this study despite the continuous IL-2 injection and not shown by Wilson et al (1989) with a shorter period of administration, might depend on a possible down-regulation of IL-2 macrophage receptors, determined by the prolonged administration of IL-2. The difference between our results and those referred by Wilson et al (1989), who described a more rapid return to baseline values with IL-2 interruption, could be due to differences in doses, route and schedule of IL-2 therapy.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…27) In other HTLV-I infected populations, a higher prevalence of mild anemia 28) and lower body mass index 29) have been reported. However, there was no significant difference in body mass index according to HTLV-I seropositivity in the present study population.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma levels of cytokines, including IL-1␤ and TNF found in various inflammatory, infectious, and malignant diseases, are often associated with hypocholesterolemia (7)(8)(9)(10)(11). Systemic infusion of cytokines has been shown to lower serum cholesterol levels in animals and humans (12)(13)(14). The concentrations of IL-1␤ and TNF similar to those found following infection induce low density lipoprotein (LDL) receptor expression in human hepatoma (HepG2) cells, and this effect is not part of its mitogenic response, as IL-1␤ did not increase DNA synthesis (15)(16)(17)(18).…”
mentioning
confidence: 99%